2016
DOI: 10.1016/j.carbpol.2016.03.077
|View full text |Cite
|
Sign up to set email alerts
|

Insightful understanding of the role of clay topology on the stability of biomimetic hybrid chitosan-clay thin films and CO2-dried porous aerogel microspheres

Abstract: Elsevier Frindy, S.; Primo Arnau, AM.; Qaiss, AEK.; Bouhfid, R.; Lahcini, M.; García Gómez, H.; Bousmina, M.... (2016). Insightful understanding of the role of clay topology on the stability of biomimetic hybrid chitosan-clay thin films and CO2-dried porous aerogel microspheres. Carbohydrate Polymers. 146:353-361. doi:10.1016Polymers. 146:353-361. doi:10. /j.cabpel.2016 Irrespective to the clay microstructure, an improvement in the mechanical properties of the 23 chitosan-clay films has been substantiated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 59 publications
1
26
0
Order By: Relevance
“…It can be explained by the highest dispersion degree of HNTs within LCS polymer matrix of the C L ‐HNTs films and subsequently highest homogeneity, confirmed by SEM analysis (Figure ). This is further supported by findings of Frindy and coworkers who studied composite films consisting of chitosan and three clay minerals: montmorillonite, sepiolite, and HNTs, and reported that their mechanical properties depend on the dispersion degree and the viscosity of the clay‐chitosan dispersion . Nevertheless, HCS‐based composite films exhibited the highest mechanical stability as a consequence of more intensive interpolymer bonding combined with intensive interactions between HCS and HNTs.…”
Section: Resultssupporting
confidence: 79%
“…It can be explained by the highest dispersion degree of HNTs within LCS polymer matrix of the C L ‐HNTs films and subsequently highest homogeneity, confirmed by SEM analysis (Figure ). This is further supported by findings of Frindy and coworkers who studied composite films consisting of chitosan and three clay minerals: montmorillonite, sepiolite, and HNTs, and reported that their mechanical properties depend on the dispersion degree and the viscosity of the clay‐chitosan dispersion . Nevertheless, HCS‐based composite films exhibited the highest mechanical stability as a consequence of more intensive interpolymer bonding combined with intensive interactions between HCS and HNTs.…”
Section: Resultssupporting
confidence: 79%
“…The elongation at break is an indicator of its extensibility. The Young’s modulus for CH films incorporated with peptide-loaded CH MPs are higher than CH films (Table 2), because the Young’s modulus increased with the increase of filler content [42], but no statistically significant differences ( P > 0.05) were found. The values obtained were low when compared with those of other oral films [43], but the composition and the evaluation methods were not the same.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve this, first the inorganic components are hybridized with the chitosan polymer using either a co-gelation or a post gelation method [66,176,177,178,179,180,181,182,184]. Chitosan-montmorillonite clay hybrid aerogels microparticles were recently reported [176,177]. In these the organic and inorganic components are well mixed together before the gelation occurred.…”
Section: State Of the Art Of Bio-aerogel Particlesmentioning
confidence: 99%
“…These hybrid aerogels have low specific surface area in comparison with chitosan aerogels. However, these hybrid aerogels showed enhanced thermal properties with the degradation delay in the order of chitosan < chitosan-graphene oxide < chitosan-clay aerogels [176,177,183].…”
Section: State Of the Art Of Bio-aerogel Particlesmentioning
confidence: 99%